Learning VMware Horizon 7 - Oven, Peter von (Packt, 2017)
"VMware Horizon 7 delivers, protects, and manages your applications and virtual desktops and ensures the end-user can access it from anywhere and at any point of time. The course will guide you from being a beginner to being able to centrally manage your desktops using VMware Horizon 7. The video starts with an overview of the architecture and latest features of VMware Horizon 7. You will also learn how to design and deploy your Horizon 7 environment. Finally, we will build out two operating systems, optimize them for your VDI, and then walk you through the different methods of delivery for the instant clone, linked clone, and full clone options. By the end of the course, you will be equipped to create desktop resources by using Horizon Desktop Pools and fine-tune the end user experience to ensure the best optimization from your virtual desktops."--Resource description page.